Study of the High-Resolution Fourier Spectrum of the ν9 and ν2 + ν7 + ν8 Bands of the С2D4 Molecule; Russian Physics Journal; Vol. 62, iss. 2 - Fomchenko A. L. Anna Leonidovna; Kuznetsov A. V. Alexey Valerevich; Zhang Fangce; Gromova O. V. Olga Vasilievna; Pashayan E. Evgeniya (2019, 2019)
Title screen